Α‐Synuclein oligomers distinctively permeabilize complex model membranes. (12th May 2014) - Stefanovic, Anja N. D.; Stöckl, Martin T.; Claessens, Mireille M. A. E.; Subramaniam, Vinod
<x xml:space="preserve">Abstract</x> α‐Synuclein oligomers are increasingly considered to be responsible for the death of dopaminergic neurons in Parkinson's disease. The toxicity mechanism of α‐synuclein oligomers likely involves membrane permeabilization. Even though it is well established that α‐synuclein oligomers bind and permeabilize vesicles composed of negatively‐charged lipids, little attention has been given to the interaction of oligomers with bilayers of physiologically relevant lipid compositions. We investigated the interaction of α‐synuclein with bilayers composed of lipid mixtures that mimic the composition of plasma and mitochondrial membranes. In the present study, we show that monomeric and oligomeric α‐synuclein bind to these membranes. The resulting membrane leakage differs from that observed for simple artificial model bilayers. Although the addition of oligomers to negatively‐charged lipid vesicles displays fast content release in a bulk permeabilization assay, adding oligomers to vesicles with compositions mimicking mitochondrial membranes shows a much slower loss of content. Oligomers are unable to induce leakage in the artificial plasma membranes, even after long‐term incubation. CD experiments indicate that binding to lipid bilayers initially induces conformational changes in both oligomeric and monomeric α‐synuclein, which show little change upon long‐term incubation of oligomers with membranes. The results of the present study demonstrate that the mitochondrial model membranes are more vulnerable to permeabilization by oligomers than model plasma membranes reconstituted from brain‐derived lipids; this preference may imply that increasingly complex membrane components, such as those in the plasma membrane mimic used in the present study, are less vulnerable to damage by oligomers.